MODEL PEMBINAAN ‘IN-HOUSE TRAINING’ SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM PENELITIAN DAN PENULISAN KARYA ILMIAH - K. Dharmawan; Y. Ramona; N. N. Rupiasi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Various attempts have been made by the government to improve the quality of teachers and quality ofeducation, such as allowances certification, training or the opportunity to continue to pursue education toMaster degree. However, these efforts have not able to improve the ability of research as mandated in theMinister Regulation PAN No. 16 Year 2009 Clause 11 that concerning the obligation of teachers in scientificpublications. To assist teachers in implementing the mandate, it is necessary to develop a model of coachingso that teachers can improve their competence and /or teacher professionalism in research. In this paper, it isdeveloped model guidance for teachers in improving the professionalism of teachers in research. The methodused in the development of this coaching model is a method of in-house training, the coaching done bysetting their respective schools, where teachers implement instructional programs. This paper is the result ofthe program community service activities are funded by DIKTI in the scheme of science and technology forsociety that was summarized in the form of coaching model through in-house training which consists of threestages approaches, namely scientific, competence, and publications. The results of this development showeda significant increase, approximately 30% on a teacher's ability to perform research of class action.